PERLINDUNGAN HUKUM TERHADAP ANAK PEREMPUAN KORBAN KEJAHATAN KESUSILAAN DI KOTA LHOKSEUMAWE - Romi Asmara; Laila M. Rasyid (Jurnal Ilmu Hukum, 2013)
Children has very central positionin the life of nation andstate,specially the nation's hope.As a chilid, needs specialtreatment in order to growreasonably good physical, mentaland spiritual, as well as the needfor legal protection if a child is inconflict with the law. Crimesagainst children, particularly girloften suffer from rape, sexualabuse and other violent sex drivebe motivated real danger thatthreatens girls, when, whereandby anyone. About this case most ofthe actor share the nearest ofExistenceoflegalvictims.protectionisstilllessthanexpectations, public system in theCriminal Code does not providefor the child's criminal victimcompensation violence relating tomorality, not because the victim'sdetection trauma cases that arenot reported, and stiffness provingto be one of the constraints facedby the apparatus law enforcement.Kata Kunci: Perlindungan Hukum, Anak Perempuan,Kesusilaan.